AS OCUPAÇÕES ESTUDANTIS SECUNDARISTAS NO BRASIL E NO ESPÍRITO SANTO (2015-2017): PROCESSO DE ENFRENTAMENTO A IMPOSIÇÃO DA REFORMA DO ENSINO MÉDIO E DA EC 95 DO GOVERNO DE MICHEL TEMER - Leal, Fernando de Oliveira (2021)
In this research, we analyzed the process of school occupations as a social movement of resistance to the neoliberal educational policies of fiscal austerity in Brazil and the state of Espírito Santo in 2015 and 2016. Based on categories such as the State, power bloc, hegemony, war of movement, and war of position, we highlight the resistance actions of students, workers, and education researchers to the movement of building hegemony of this educational policy arising from the power bloc. Initially, we developed documentary analysis from different sources (official, business media, alternative media, social movements, and their repercussions on social networks) that account for the processes of formulating neoliberal reforms focused on the last stage of basic education. In addition, we interviewed 04 important leaders, protagonists of the occupation processes in 04 high schools located in the Vitória metropolitan zone, which were relevant for the size and strength of the occupation process. In this context, we mapped, identified, and analyzed the organized reactions of the student movement that, at the national and local levels, faced the hegemonic consequences of approval and implementation of the PEC's expenditure ceiling and the reform of secondary education in Brazil and Espírito Santo. In Brazil, there were hundreds of occupations between 2015 and 2016, in at least six states, especially São Paulo. At the end of 2016, thousands of schools were occupied, especially in the state of Paraná, with around 850 occupations. In Espírito Santo, there were several forms of struggle for education, led by various social subjects of popular origin between 2015 and 2016. Thus, at the end of 2016, Espírito Santo students occupied about 71 public schools, in addition to 03 Ifes campuses and 16 Ufes buildings. The entry on the scene of these young political subjects, of working origin, especially in low-paid jobs, especially women, blacks, LGBT youths, brought the occupation of schools as a new form of struggle in education, enhancing student self-organization, democratic debate, the broad involvement of diverse democratic sectors in setting up a rearguard for the occupational movement and experimenting with accountability for their school, and managed to breathe new life into the struggles for Brazilian education and, in unity with other social sectors, can mean a qualitative change in the class struggle. Thus, even if the broad articulation of medium stratus, of private hegemonic apparatus and ideological and coercive State apparatus, under the aegis of the power bloc, to dismantle and repress students, has managed to guarantee the approval of Law 13.415/17 and the Constitutional Amendment 95/17, the students were able to expand their forces, engaging new subjects in social struggles, guaranteeing some small setbacks in the law on the reform of secondary education, in comparison with the initial MP. In Espírito Santo, the occupations helped to produce an important recompositing of the forces of the power bloc, culminating in the resignation, by PH, of running for re-election and in the election of Renato Casagrande (PSB), who revised many positions of the educational project, delaying the implementation of the reform of high school at the local level, weakening the legitimacy of the Escola Viva Program and reducing the interference of the ES em Ação business movement within Sedu.